Ang Kapaligiran ng Metro Manila [videorecording] mga suliranin at hinaharap. (Quezon City DENR Environmental Management Bureau)
Studies the pollution problems of Metro Manila.
Keywords: Pollution -- Manila Metropolitan area; Environmental policy -- Manila Metropolitan area; Environmental protection -- Manila Metropolitan area